The Effect of Accounting Information Systems to Facilitate Supply Chain Management in Retail Companies: Evidence form Indonesia - Dwiarso Utomo; Entot Suhartono; Zaky Machmuddah (International Journal of Supply Chain Management, 2020)
Abstract— This study aims to determine the effect of the ability of users of Accounting Information Systems (AIS) to improve the Supply Chain Management (SCM) performance, the involvement of users of AIS, and top management support on the performance of AIS in retail companies. The population in the study were 23 retail companies in the Central Java Region. The sample in this study amounted to 69 respondents. The sampling technique in this study was purposive sampling. Data collection was done through a questionnaire and data were analyzed using multiple linear regression analysis. Based on the results of the analysis that has been done, there is a significant influence between the independent variables on the performance of AIS at retail companies in the Central Java region simultaneously. Whereas partially, the information system user capability and top management support had a significant effect on the performance of AIS, on the contrary the information system involvement variable did not significantly influence the performance of AIS in retail companies in the Central Java region.